Securing library information system: Vulnerabilities and threats - Mohamad Tahir, Hatim; Puteh, Nurnasran; Husin, Mohd Zabidin; Md. Said, Abas (2010)
Threats and vulnerabilities in computers and networks are common nowadays since computers are widely used by the public. The risks of computer threats and vulnerabilities are high since most computers are connected to the internet. Library Information Systems is also vulnerable to attack since it is a public access institution. Majority of users are naive when it comes to computer and network securities. Some breaches in Library Information System are intentional and some are unintentional. Risks analysis should be done to find the threats and risks in designing the Library Information System. Threats are made possible due to lack of proper procedures, software flaws and policies. The administrators should anticipate all the possible attacks and their mitigation techniques. In this paper, we will try to address various issues arise from this vulnerabilities and threats. We will also describe how we can reduce and overcome this vulnerabilities and threats.